4-(Dimethylamino)pyridinium dibromidotriphenyl-stannate(IV). - Norhafiza, I.; Lo, K.M.; Ng, S.W. (International Union of Crystallography, 2008)
The anion in the title salt, (C(7)H(11)N(2))[SnBr(2)(C(6)H(5))(3)], lies on a twofold rotation axis that passes through the metal atom as well as the C(ipso)-C(para) atoms of one of the aromatic rings. The metal center is five-coordinate in a trans-Br(2)SnC(3) trigonal bipyramidal geometry. The cation is disordered about a center of inversion.